Design of optimization strategy-based halal supply chain at a meat market in Indonesia - Fahadha, Rizqa Ula; Sutarto, Sutarto (Faculty of Business & Economics, Universitas Islam Indonesia, 2025)
Purpose – To design an integrated halal risk mitigation strategy for the chicken meat supply chain of Indonesia. The primary focus is on identifying critical points that have the potential to threaten halal integrity from upstream to downstream in the supply chain.Methodology – This research approach uses a combination of Failure Mode and Effects Analysis (FMEA) methods to identify and measure the level of risk at each stage of the supply chain, and Analytic Hierarchy Process (AHP) to determine the priority of mitigation strategies based on expert perspectives. Findings – The results showed that the poultry slaughterhouse stage is the most critical point in maintaining halal products, with a priority weight of 0.51, followed by farms (0.30), and retail (0.19). The main risks identified included uncertainty in the validation of the slaughter method, non-compliance of feed and medicine with halal standards, and weak traceability of product origin in retail. Implications – This research provides strategic contributions for policymakers, halal certification institutions, and business actors to strengthen the governance of the national halal supply chain. Applying the research results can improve the effectiveness of supervision and ensure compliance with Sharia principles as a whole.Originality – The uniqueness of this study lies in integrating the FMEA and AHP methods in the context of the halal supply chain, which is still limited in Indonesian literature. This approach offers an evidence-based strategic framework for systematic and sustainable halal risk management.